The gut–bone axis: mechanisms through which oleic acid regulates bone metabolism and its potential in preventing and treating osteoporosis - Zhu, Minshun; Zhang, Xianda; Zhang, Jianhua; Chen, Jiaping; Liang, Long (Frontiers in Nutrition, 2026)
Osteoporosis is a prevalent metabolic bone disorder characterized by reduced bone mass and increased fracture risk, posing a growing global health burden. Dietary factors have emerged as important modulators of bone metabolism, among which the monounsaturated fatty acid (MUFA) oleic acid—abundant in olive oil and nuts—has attracted increasing attention. This review summarizes current evidence on the mechanisms through which oleic acid influences bone metabolism, with particular emphasis on the gut–bone axis as an integrative regulatory pathway. We describe how oleic acid modulates gut microbiota composition, reinforces intestinal barrier integrity, and influences the production of microbiota-derived metabolites, including short-chain fatty acids (SCFAs), bile acids, and indole derivatives. These metabolites act on bone remodeling through specific signaling pathways and receptors, such as free fatty acid receptors, bile acid receptors, and the aryl hydrocarbon receptor (AhR), thereby linking dietary fat intake to skeletal homeostasis. Preclinical and clinical evidence supporting the bone-protective effects of oleic acid–rich dietary patterns is critically evaluated, while existing gaps—particularly the limited availability of randomized controlled trials using purified oleic acid—are highlighted. Finally, challenges and future directions are discussed, including interindividual variability in gut microbiota, translational limitations, and the potential for personalized nutrition strategies. Collectively, current evidence suggests that oleic acid represents a promising dietary component for supporting bone health, with the gut–bone axis providing a mechanistic framework for future research and potential translational exploration.